Web-Based School Information System Using the Laravel Framework as a Platform for Information and Promotion at High Schools - Vita Ulvita Sari (COREAI: Jurnal Kecerdasan Buatan, Komputasi dan Teknologi Informasi, 2026)
This study aims to design and implement a web-based school information system application as a medium for disseminating information and a promotional tool at PGRI Purwoharjo High School. The problem faced is the limitation of information dissemination, which remains conventional and is therefore ineffective and inefficient in reaching the wider community. The research method employed the System Development Life Cycle (SDLC) using the Waterfall model, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The system was developed using the Laravel framework, which supports structured and dynamic data management. The results of this study show that the developed system is capable of effectively providing information services, including school profiles, news, announcements, and online registration services for new students. In addition, this system also serves as a promotional medium capable of enhancing the school’s visibility and image within the community. Thus, the implementation of this web-based information system is expected to improve the quality of information services and support digital transformation within the school environment.